Hubungan antara Awareness Iklan melalui YouTube dengan Minat Beli Viewers - Denita Bayu Gita; Indri Rachmawati (Bandung Conference Series: Communication Management, 2022)
Abstract. Along with the times, currently, there are various types of advertising in providing information about products and brands that are market to get the attention of consumers. Advertising is one of the most effective types of mass communication used for marketing. Attractiveness through advertising is an effort made by advertisers to increase the number of customers. There is one streaming application that is currently favored by the public in providing entertainment during their spare time, namely the Netflix application. The streaming application carries out a strategy in marketing by promoting through YouTube social media to attract consumers to subscribe. The purpose of this study was to determine the relationship between awareness of Netflix application advertisements and interest in buying subscription viewers in the millennial generation, to determine the relationship between trial Netflix application advertisements and purchase intentions of viewers to subscribe to the millennial generation, and to determine the relationship between Netflix application advertising reinforcement and purchase interest. viewers subscribe to the millennial generation.The quantitative method used is by using a correlational approach to test whether or not there is a relationship between the two variables. In addition, the method used in this research is a survey by distributing questionnaires through Google Forms with descriptive analysis techniques to compare existing conditions and test hypotheses. The results of this study there is a relationship between Netflix application advertisements on YouTube social media with viewer buying interest with the Spearman Correlation Test results of 0.549. Abstrak. Seiring dengan perkembangan zaman, saat ini terdapat periklanan yang beragam dalam memberikan informasi mengenai produk maupun merek yang dipasarkan untuk mendapatkan perhatian dari konsumen. Iklan menjadi salah satu jenis komunikasi massa yang efektif digunakan untuk melakukan pemasaran. Daya tarik melalui periklanan menjadi usaha yang dilakukan oleh pengiklan untuk menambah jumlah pelanggan. Terdapat salah satu aplikasi streaming yang saat ini digemari oleh masyarakat dalam memberikan hiburan saat waktu senggang yaitu aplikasi Netflix. Aplikasi streaming tersebut melakukan strategi dalam pemasaran dengan melakukan promosi melalui media sosial YouTube untuk menarik minat konsumen agar berlangganan. Tujuan dalam penelitian ini Untuk mengetahui hubungan antara awareness iklan aplikasi Netflix dengan minat beli viewers berlangganan pada generasi milenial, untuk mengetahui hubungan antara trial iklan aplikasi Netflix dengan minat beli viewers berlangganan pada generasi milenial, dan untuk mengetahui hubungan antara reinforcement iklan aplikasi Netflix dengan minat beli viewers berlangganan pada generasi milenial. Metode kuantitatif yang digunakan yaitu dengan menggunakan pendekatan korelasional untuk menguji ada atau tidaknya hubungan antara kedua variabel tersebut. Selain itu, metode yang dilakukan pada penelitian ini yaitu survei dengan menyebarkan kesioner melalui Google Forms dengan teknik analisis deskriptif untuk membandingkan kondisi yang ada serta menguji hipotesis. Hasil penelitian ini adalah terdapat hubungan antara awareness iklan melalui YouTube dengan minat beli viewers dengan hasil Uji Korelasi Spearman sebesar 0,549.